Penerapan model pembelajaran koopertatif tipe talking stick untuk meningkatkan pemahaman konsep hak dan kewajiban sebagai warga masyarakat kelas IV sekolah dasar - Ahmad Baihaqi; Hasan Mahfud; Fadhil Purnama Adi (Universitas Sebelas Maret, 2020)
This study aims to improve the understanding of the rights and obligations of community members by applying the Talking Stick cooperative learning model. This research is a Classroom Action Research with two cycle. The subjects of this study were fourth grade student of Mangkuyudan elementary school number 02 Surakarta with total of 28 students. This study uses data collection technique in the form of observations, documentation, field notes, tests, and. And interviews uses qualitative and quantitative data analysis. The first cycle of the second meeting produced a percentage of 52,17% classically, and the study continued with the second cycle of the second meeting with percentage of 83,33% classically. Based on the results of the study, it can be concluded that the ability to improve the understanding of the concept of rights and obligatons of community members in grade 4 students of Mangkuyudan elementary school number 02 Surakarta in the academic year 2019/2020 can be improved through the cooperative learning model of the Talking Stick type.